Benchmarking Western Balkan Economies - Stošić, Ivan; Minović, Jelena (Industrija, 2014)
The aim of this paper is to analyse the relative positions of Western Balkan countries and to determine the differences or similarities in the results based on survey data (of international institutions: EBRD, World Bank, World Economic Forum, Heritage Foundation), and on based on selected key statistical indicators. Using the sample of countries in same region and by applying the method of “multi-country” statistical analysis, it was attempted to establish relation between results obtained in studies of international institutions, and some actual achieved key economic performances by the first measure of correlation (so-called Spearman's coefficient of correlation). The obtained results differ to a smaller or greater extent according to the experiential test we used in the case of this region. Therefore, our findings reveal that overall economic position of selected country cannot be perceived only by relying on one methodology or type of data. Consequently, we point out that multi-criteria are a must and each methodology can be useful, because it emphasizes different aspects of the economic performances and country position.
Keywords: Benchmarking; macroeconomic indicators; competitiveness indicators; Western Balkan